2013
DOI: 10.1111/pce.12089
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and acclimation of leaf gas exchange in a piñon–juniper woodland exposed to three different precipitation regimes

Abstract: Leaf gas-exchange regulation plays a central role in the ability of trees to survive drought, but forecasting the future response of gas exchange to prolonged drought is hampered by our lack of knowledge regarding potential acclimation. To investigate whether leaf gas-exchange rates and sensitivity to drought acclimate to precipitation regimes, we measured the seasonal variations of leaf gas exchange in a mature piñon-juniper Pinus edulis-Juniperus monosperma woodland after 3 years of precipitation manipulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
123
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 89 publications
(140 citation statements)
references
References 68 publications
13
123
3
Order By: Relevance
“…In ecosystems facing severe spells of drought, plant assimilation is strictly dependent on water availability [42][43][44][45], whose duration controls the length of the growing season [46][47][48]. In this study, photosynthesis showed a strong seasonal variation, as confirmed by the significant correlation of Anet Table A3. SIR and total El-FAME were both significantly mostly correlated with SR h , with the exception of carbohydrates and amino acids, and fungi and protozoa respectively (Table 4).…”
Section: Discussionsupporting
confidence: 64%
“…In ecosystems facing severe spells of drought, plant assimilation is strictly dependent on water availability [42][43][44][45], whose duration controls the length of the growing season [46][47][48]. In this study, photosynthesis showed a strong seasonal variation, as confirmed by the significant correlation of Anet Table A3. SIR and total El-FAME were both significantly mostly correlated with SR h , with the exception of carbohydrates and amino acids, and fungi and protozoa respectively (Table 4).…”
Section: Discussionsupporting
confidence: 64%
“…), while also maintaining low, but significant canopy gas exchange even as Ψ s and Ψ PD declined down to values of −6 to −7 MPa during drought (Limousin et al. 2013). Predawn water potential ( Ψ PD ) in piñon deviated significantly from soil water potential ( Ψ s ) during periods of drought (Fig 2…”
Section: Resultsmentioning
confidence: 99%
“…For each species, a single regression relationship was fit across treatments (see Limousin et al. 2013 for details on the gas exchange sampling effort).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some aspects of these shrubs (e.g., root depth) may have acclimatized over the ca. 50-year history of the snow fences to the effect of snow depth treatments on soil moisture availability (Atkin et al 2000;Limousin et al 2013;Luo et al 2001). These shrubs are deeply rooted and can utilize soil water to 2-to 3-m depth (Caldwell et al 1998;Peek et al 2005;Ryel et al 2004) though our measurements of soil moisture only extended to 100-cm depth.…”
Section: Discussionmentioning
confidence: 98%